Effects of Bothrops asper (terciopelo) myotoxin III, a basic phospholipase A2, on liposomes and mouse gastrocnemius muscle - Bultrón, Euris (1993)
The action of Bothrops asper myotoxin III, a basic phospholipase A2 which induces acute muscle damage, was studied in mouse gastrocnemius muscle in vivo and in vitro and in multilamellar liposomes. Myonecrosis occurred rapidly after myotoxin injection, as indicated by histological alterations and by a drastic increment in plasma creatine kinase levels. A dose-dependent release of creatine kinase from mouse gastrocnemius muscle incubated in vitro with the toxin was observed. Myotoxin III affected negatively charged multilamellar liposomes, as evidenced by the release of peroxidase trapped in the vesicles. In contrast, very little effect was observed on positively charged vesicles. When gastrocnemius muscle or liposomes were incubated at 4 degrees C there was no membrane-disruptive effect. Inhibition of phospholipase A2 activity, by elimination of calcium and addition of EDTA, resulted in a significant, but not total, reduction in both muscle-damaging and liposomal disrupting effects. It is proposed that B. asper myotoxin III affects cellular and artificial membranes inducing prominent alterations in membrane permeability to ions and macromolecules. Membrane-disrupting activity is probably related to a molecular region different from the catalytic site, although enzymatic activity greatly enhances myotoxin action.